Social Graphic Design and its Reflections on The Practices of The Saudi Designer in Designing Awareness Posters (Al-Academy, 2023)
The concept of social graphic design is one of the most critical areas that highlight the designer's knowledge of social responsibility by employing design skills in community awareness. This study focused on defining social graphic design, the meaning, practices, and strategies for designing awareness posters. This study reviewed two examples of awareness posters that reflect the Saudi designer's practices. The results summarized that social graphic design is a concept not taught directly but gained from permanent practice in designing awareness posters that interact with community issues. The designer's understanding of his social events and their sensing in the visual form of a poster reflects the designer's social awareness. Social graphic design plays several roles and functions that significantly address and define societal phenomena, behaviours, and toxic habits in society. Therefore, it is essential to address the concept of social design in design research by interpreting its various theories and studies.